Nosečnost in porod pri mladostnicah - Palancsai-Šiftar, Janka (Zdravniški vestnik, 2003)
Background. Adolescence is the period between childhood and adulthood. In adolescence a higher incidence of complications in pregnancy and during labouris noted, especially a higher number of preeclampsia, anemia, preterm labours, very low birth-weight infants and/or too small for gestational age infants. However, where antenatal care has been given more attention, the number of the above mentioned complications in the course of pregnancy and labour has in adolescents not been so high. In the region of Pomurje there is a lot of primiparous adolescents under twenty years of age in comparison to other regions of Slovenia. In the present work I have investigated the complications in pregnancy, during labour, with newborns and the characteristics of antenatal care for adolescents. Methods. The analysis is based on the data taken from the Perinatal Informational System of Slovenia for the six years (1987-1992). The register is uniform for the total teritory of Slovenia since 1986. The data collected are the data about the pregnancy and delivery, about post-delivery period and about the newborn. In the study group the primiparous adolescents, aged up to 19 years were included. The control group consisted of primiparas in the age group 20-34 years. Results. The study included 3553 primiparas. There were 786 (22.1%) primiparus adolescents in the study group; and 2767 (77.9%) women aged 20-34 years in thecontrol group. The results show that the number of labours decreased in both the study and the control group. Adolescents care less for antenatal examinations, a higher percentage of them is single and have accomplished fewer years of education. In pregnancy the incidence of anemia is higher, and the percent of intrauterine growth retardation is significantly higher in the control group. (Abstract truncated at 2000 characters).
Keywords: Adolescenca; Adolescence; Adolescent Health Services; Adolescentne, zdravstvene službe; childbirth; Dejavniki tveganja; human pregnancy; Labor; mladostnice; Nosečnost; Nosečnost mladoletnic; Porod; Pregnancy; Pregnancy In Adolescence; Risk Factors